ANALYZING COLLAGE AS A COMMUNICATION ACT IN THE DIGITAL AGE BASED ON THE DADAISM RENEWAL MOVEMENT'S SPIRIT - Dewi, Agustina Kusuma; Dwinaya, Levita (International Journal of Humanity Studies (IJHS), 2024)
Collage combines the semiotic tradition of Roland Barthes, the phenomenological tradition of Edmund Husserl, the critical tradition of Karl Marx, and the point of view of Jurgen Habermas in visual communication. The collage technique creates trans-aesthetic elements and double codes, a Dadaist method of encoding signs. Building on previous research, this study explores collage art as a communication act and its process in the digital era. Digital photography technology and computer software facilitate quicker and easier creation of collage art, emphasizing the fundamental concept of "paste." This pasting-sticking process mirrors the communication process of art and design in the digital era, illustrating cyclical communication capable of transcending space and time. The research has several conclusions. (1) By enhancing visual communication strategies and efficiency based on the spirit of the Dadaism renewal movement, unique collages can be created as a personal sign of message(s). (2) Collages as communication act in the digital era represent dialogue in trans-aesthetics code. (3) On the other hand, with the spirit of Dadaism that contains a free mind, open creation, and emphasis on social-cultural issues, collages as a communication process are also possible to frame messages and create fallacy.